PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS V SD INPRES BONTOALA II KABUPATEN GOWA - Nurfaizah Ap; Latri; Sri Sul Aprilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on the critical thinking skills of fifth-grade students at SD Inpres Bontoala II Gowa Regency in Pancasila Education subject. This study was based on initial observations showing that students tended to be passive and less capable of identifying and analyzing the core problems, indicating low critical thinking skills due to conventional learning methods. Using a quantitative approach with a quasi-experimental design of the nonequivalent control group type, this study involved the entire population of fifth-grade students at SD Inpres Bontoala II Gowa Regency. The research sample consisted of 22 students from class VA as the experimental group and 22 students from class VB as the control group, selected using a purposive sampling technique. Data collection was carried out using critical thinking skills test sheets and PBL model implementation observation sheets. Data analysis was performed descriptively and inferentially. The research results showed that (1) the implementation of the PBL model in the experimental group proceeded very well, with a significant increase in teacher and student observations from the